Central Banking in Lebanon; A Central Bank for The Economic Development of The Country - Asseily, Antoine Edouard (Beirut, Khayat Book & Publishing, 1967)
This book is an analysis and appraisal of the newly established Central Bank in Lebanon.
Bibliography: p. 197-202.
osc 7/8/17
Loans
Keywords: Banks and Banking, Central; Banks and Banking